Historicity, memory and writing of History: Augustus and the ‘culto della romanità’ during the fascist ‘ventennio’ - Silva, Glaydson José da (Romanitas - Revista de Estudos Grecolatinos, 2018)
Only recently different fronts of study on the culto della romanità during fascism begun to be better explored; for instance, the idea that romanity itself would or could serve a project of modernity in Fascist Italy. The place occupied by the myth of Rome in the collective imaginary and the role of institutions – and of historians and archaeologists, in particular – have also received special attention. Initially thought as an instrument to be used in classroom (in the discipline of Introduction to Ancient and Medieval History at the Federal University of São Paulo), this article works with a number of examples linked to the culto della romanità that mobilized above all the figure of Roman emperor Augustus during the fascist years. Such mobilization occurred especially on occasion of the celebrations around the two-thousandth Jubilee of the princeps’ birth, including the Mostra Augustea della Romanità and an intricate historical and archaeological plot linked to the area around Augustus’ Mausoleum and the restoration and moving of the Ara Pacis altar. The idea is that this text may serve as an instrument capable of stimulating reflections on historicity, memory and the writing of history in connection with Ancient Rome.
Keywords: Rome; Augustus; Fascism; Culto della romanità; Mostra Augustea della Romanità